Development of Moodle E-Learning in Learning Human Reproductive System in Junior High School - Monlinia, Yuyu; Akyuni, Quratul; Kaewkanlaya, Piyada; Asril, Zainal (International Journal of Multidisciplinary Research of Higher Education, 2024)
This study aims to analyze the development of Moodle-based e-learning on human reproductive system material for junior high school students. The type of research developed is Research and Development (R&D) with the 4D development model. This model consists of 4 stages, namely defining, designing, developing, and disseminating. Meanwhile, this research focuses only on the definition stage. The analysis of the definition stage carried out, namely: front-end analysis, learner analysis, task analysis, concept analysis, specifying instructional objectives. The research subjects consisted of thirty students and one junior high school science teacher. Data collection techniques through observation in the form of interviews and filling out questionnaires by students. Based on the results of the research and discussion that has been presented, it is necessary to develop alternative learning media, namely Moodle-based e-learning on human reproductive system material for junior high school students.